The Application Of The Principle Of Bank Secrecy In The Process Of Eradicating Money Laundering Criminal Offences Based On Aspects Of Legal Certainty - Rahman Maulana, Dyo; Ahmad Sholikhin Ruslie (International Journal of Social Sciences and Humanities, 2024)
Bank secrecy is the core of a banking system policy and is based on the "prevalence" of general banking practices. The problem in the prevention of money laundering is basically still a challenge and will be difficult in the handling process, it is because the Law on Money Laundering has not been maximally able to take legal action, not to mention the existence of strict bank secrecy principle rules in the relevant country. This research aims to examine the application of the principle of bank secrecy in the process of eradicating the criminal offence of money laundering in the aspect of legal certainty. The research method used in this research is normative juridical with the approach used Legislation approach and conceptual approach. The conclusion of this research is that bank secrecy is no longer the main reason for banks to refuse or delay providing information requested by law enforcement officials. The bank must comply with the procedures and mechanisms that have been established by law in order to avoid abuse of the principle of confidentiality for improper purposes. In the process of implementing money laundering criminal offences, it is necessary to run in a balanced, fast, and precise manner with effective law enforcement efforts. In addition, a structured and confidential information exchange mechanism between banks and law enforcement is important to strengthen the investigation and investigation process.